HUBUNGAN SINDROM METABOLIK DENGAN KEJADIAN DISFUNGSI EREKSI PADA PASIEN PRIA DIABETES MELITUS TIPE 2 DI POLIKLINIK PENYAKIT DALAM RSUP SANGLAH DENPASAR - Maratni, Ni Putu Tesi (E-Jurnal Medika Udayana; vol 5 no 3(2016):e-jurnal medika udayana, 2016)
ASSOCIATION OF METABOLIC SYNDROME WITH ERECTILE DYSFUNCTION IN TYPE 2 DIABETES MELLITUS MEN PATIENTS AT INTERNAL MEDICINE OUTPATIENT CLINIC OF SANGLAH GENERAL HOSPITAL DENPASAR Erectile dysfunction (ED) is a commonly chronic complication among men with type 2 diabetes mellitus (T2DM). The associated factor of diabetes-induced erectile dysfunction is metabolic syndrome. This research is designed to observe the relationship of metabolic syndrome and ED in T2DM patients. This cross sectional study has 34 consecutive samples and is conducted at Internal Medicine Outpatient Clinic of Sanglah Hospital in November and December 2013. ED is diagnosed based on The International Index of Erectile Function 15 (IIEF 15) questionnaire. Metabolic syndrome is diagnosed based on revised NCEP ATP III criteria. Demographic data and laboratory results are taken from medical records. Data are analyzed by chi square bivariate test. The results showed metabolic syndrome does not correlate significantly with ED among T2DM patients (p=0.913; 95% CI 0.082–10.228).
Keywords: Metabolic syndrome; Erectile dysfunction; Type 2 diabetes mellitus